Digital learning and extending electoral authoritarianism in Singapore. Issue 6 (17th August 2020) - Tan, Netina
ABSTRACT: This study demonstrates how a hegemonic party learns from its early missteps to become an adept social media user, competing and expanding its digital influence. Singapore's long-standing People's Action Party (PAP) government has extended existing laws and co-opted social media as an information tool to shape public opinion and repress dissent. Its digital innovations include hiring social media consultants, "Internet Brigade" and "influencers" to soft-sell public policies and counter anti-establishment online comments. Based on a comparative analysis of four Facebook activities of four key political parties over the last decade, this study finds Facebook use to have raised electoral competitiveness, albeit temporarily. Singapore's evolving legal framework, coordinated media strategy and lack of transparency governing digital campaign tools enabled the PAP to overtake the opposition parties in expanding social network. Singapore demonstrates how digital authoritarianism can be advanced in subtle, covert ways.